2016
DOI: 10.1017/rdc.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

First Radiocarbon Chronology for Mwoakilloa (Mokil) Atoll, Eastern Caroline Islands, Micronesia

Abstract: Given their sheer number and evidence for long-term prehistoric occupation, atolls occupy a unique position in the peopling of the Pacific. However, they have frequently been overlooked in favor of larger islands due to a host of logistical and other issues. Once viewed as marginal environments, current research is now showing that small islands like these may have been more attractive to settlers than once thought. A new research program in Micronesia is dedicated to examining atolls to better develop baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…These early dates for settlement on, or at least sustained use of, Pingelap atoll support a growing body of literature (e.g., Dye 1987;Riley 1987;Rosendahl 1987;Weisler 1999aWeisler , 2001aWeisler , 2001bYamaguchi et al 2005;Weisler et al 2012;Thomas 2015;Poteate et al 2016;Lambrides and Weisler 2018;Carson 2018;Harris and Weisler 2018) indicating that atolls were settled quite early in the colonization process of central and eastern Micronesia. Atolls may have played an important role as "stepping stones" in earlier migrations, and people on high islands would have encountered them during long-distance seafaring expeditions as the region became settled, giving them a chance to exploit the available resources and evaluate an atoll's potential for more permanent settlement.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These early dates for settlement on, or at least sustained use of, Pingelap atoll support a growing body of literature (e.g., Dye 1987;Riley 1987;Rosendahl 1987;Weisler 1999aWeisler , 2001aWeisler , 2001bYamaguchi et al 2005;Weisler et al 2012;Thomas 2015;Poteate et al 2016;Lambrides and Weisler 2018;Carson 2018;Harris and Weisler 2018) indicating that atolls were settled quite early in the colonization process of central and eastern Micronesia. Atolls may have played an important role as "stepping stones" in earlier migrations, and people on high islands would have encountered them during long-distance seafaring expeditions as the region became settled, giving them a chance to exploit the available resources and evaluate an atoll's potential for more permanent settlement.…”
Section: Discussionsupporting
confidence: 76%
“…Project personnel determined the locations of test units based on the intention to construct a preliminary settlement history for Pingelap and to examine land use practices ( Figure 3). Following procedures from previous atoll studies (e.g., Thompson 2010;Poteate et al 2016), which have indicated that points of high elevation on atolls are likely to represent long-term settlement and that central areas have the longest occupation because of a larger freshwater lens (e.g., Riley 1987;Best 1988;Weisler 1999a;Yamaguchi et al 2005;Thomas 2009;Figure 3 Test unit and shovel test locations. Drafted by Joel Butler.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an archaeological excavation showed that Mwoakilloa (Mokil) atoll in Eastern Micronesia was settled as early as 1700~1500 BP(Poteate et al 2016). This data likewise the data from this paper indicates that the timing of settling small coral islands was slightly later but not considerably later than high islands nearby.…”
supporting
confidence: 84%
“…In the Pacific, some of the gaps in our knowledge of small island colonization and adaptations have been filled by work on atolls or small limestone islands in Micronesia, including the Marshall Islands (e.g., Weisler 2001aWeisler , 2001bWeisler , 2002Weisler et al 2012;Yamaguchi et al 2009), Mwoakilloa (Poteate et al 2016), Fais (Intoh 2008;Intoh and Shigehara 2004), Kiribati (e.g., Thomas 2007aThomas , 2007bThomas , 2009Thomas , 2014, and Palau (e.g., Clark 2005;Clark et al 2006;Fitzpatrick 2003;Fitzpatrick et al 2011). There are also many other similar ones in Polynesia such as the Cook Islands (e.g., Allen and Craig 2009; Allen and Steadman 1990; Allen and Wallace 2007; Kirch et al 1995), the Tuamotu archipelago (e.g., Conte and Dennison 1995), the remote islands of Henderson, Pitcairn (Weisler 1995), and Rapa Nui (e.g., Hunt and Lipo 2011), and even the Arawe Islands of Papua New Guinea (Specht et al 2016), all of which have enhanced our understanding of small island adaptations.…”
Section: The Pacificmentioning
confidence: 99%